Inertial Measurement Unit-Assisted Implantation of Pedicle Screws in Combination With an Intraoperative 3-Dimensional/2-Dimensional Visualization of the Spine. Issue 3 (30th May 2018) - Jost, Gregory F; Walti, Jonas; Mariani, Luigi; Schaeren, Stefan; Cattin, Philippe
Abstract: BACKGROUND: Inertial measurement units (IMUs) are microelectromechanical systems used to track orientation and motion. OBJECTIVE: To use instruments mounted with IMUs in combination with a 3- and 2-dimensional (3D/2D) rendering of the computed-tomography scan (CT) to guide implantation of pedicle screws. METHODS: Pedicle screws were implanted from T1 to S1 in 2 human cadavers. A software application enabled the surgeon to select the starting points and trajectories on a 3D/2D image of the spine, then locate these starting points on the exposed spine and apply the IMU-mounted instruments to reproduce the trajectories. The position of the screws was evaluated on the postoperative CT scan. RESULTS: A total of 72 pedicle screws were implanted. Thirty-seven (77%) of the thoracic screws were within the pedicle (Heary I), 7 (15%) showed a lateral breach of the pedicle, and 4 (8%) violated the anterior or lateral vertebral body (Heary III). In the lumbar spine and S1, 21 screws (88%) were within the pedicle (Gertzbein 0), 2 (8%) screws had a pedicle wall breach < 2 mm (Gertzbein 1), and 1 > 2 to < 4 mm (Gertzbein 2). In the second cadaver, the position was compared to the intraoperatively shown virtual position. The median offset was 3°(mean 3° ± 2°, variance 5, range 0°–9°) in the sagittal plane and 3° (mean 4° ± 3°, variance 9, range 0°–12°) in the axial plane. CONCLUSION: IMU-assisted implantation of pedicle screws combined with an intraoperative 3D/2D visualization of the spine enabled the surgeon to precisely implant pedicle screws on the exposed spine.